Context and determinants for implementing a sepsis survivor care transition intervention reported from five health systems and home health agencies - Bowles, Kathryn H.; Stawnychy, Michael A.; O'Connor, Melissa; Mikkelsen, Mark E.; Hodgson, Nancy; Sang, Elaine; You, Sang Bin; Pitcher, Katherine; Song, Jiyoun; Oh, Sungho; Newman, Brittany; Garren, Patrik; et al. (Frontiers in Medicine, 2025)
IntroductionCare transitions from acute to post-acute care are complex, especially for sepsis survivors. Implementation science offers valuable insights to translate best practices and improve care transitions. Our objective is to explore the context (site characteristics and personnel) and determinants (barriers, proposed strategies, and facilitators) influencing I-TRANSFER, a Type 1 hybrid implementation science study aimed at providing timely home health and outpatient visits for sepsis survivors within 1 week of hospital discharge.MethodsQualitative, descriptive design with interviews guided by the eight study objectives and the Consolidated Framework for Implementation Research. Ninety-one leaders in clinical, quality, and administrative roles caring for sepsis survivors in five healthcare systems (16 hospitals) and five affiliated home health care agencies in four states participated. Deductive and inductive thematic analysis of 61 interviews conducted using NVivo 14. Proposed strategies were mapped to the Expert Recommendations for Implementing Change (ERIC) taxonomy.ResultsA total of 32 themes emerged. Barriers included care coordination, staffing, electronic health record (EHR), information transfer, and access to care. Informants proposed ERIC strategies to address barriers such as changing record systems, facilitating relay of clinical data to providers, conducting education meetings, or revising professional roles. Facilitators occurred across several themes: EHR; information transfer; staffing; care coordination; access to care; home health policies, pathways, and processes; and quality monitoring.ConclusionThe interviews produced actionable insights for leaders, clinicians, providers, and policy makers regarding identifying sepsis through clear definitions, using the problem list and ICD-10 coding. Scheduling outpatient care, communicating to the next level of care, and providing timely follow-up and care coordination necessitates attention to staffing, tools for scheduling and quality measurement, and EHR integration for information transfer. Patient education is critical for awareness of risk and informed decision-making regarding follow-up after discharge.